COASTAL USE CHANGE ANALYSIS, STUDY CASE: JAKARTA RECLAMATION PROJECT - Ilham Armi; Wiwin Windupranata; Agung Budi Harto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Jakarta Bay is a very strategic area but with various problems. The reclamation project is expected to address various problems in the area. So, it is necessary to study whether the reclamation project is affecting the bay of Jakarta. One that can be researched is land-use change, in this case coastal use, to know whether there is any change in the land function in Jakarta bay. It can also be examined whether a reclamation project that has been going on so far will have an effect on some aspects of the area, either with its current state or in the future. To know the change of coastal land function, one of possible method is satellite image. Landsat satellite images can be used as data to see and compare whether there are changes in the function of coastal land in the bay area of Jakarta. From the results, it is known there are some changes in the function of land, although still limited to the islands of reclamation. Then by analyzing a number of aspects, it is known that the reclamation project will give some positive influence on the condition of the Jakarta Bay.